To serve patients is our greatest privilege - David Feinberg (The Beryl Institute, 2014)
In his guest editorial, Dr. David Feinberg of UCLA Health System reminds us of the power of patient voice and the lessons we should be open to learning from those we serve every day. He offers, "It is a blessing for us to work in an environment where we have the opportunity every day to touch someone's life so deeply. We must never lose sight of that. It is our responsibility to not just treat our patients, but also to embrace them."